A Rare Cause of Acute Pancreatitis: Intramural Duodenal Hematoma. (4th October 2012) - Goyal, Hemant; Singla, Umesh; Agrawal, Roli R.
Abstract : We describe an interesting case of intramural duodenal hematoma in an otherwise healthy male who presented to emergency room with gradually progressive abdominal pain, nausea, and vomiting. This condition was missed on initial evaluation and patient was discharged from emergency room with diagnosis of acute gastritis. After 3 days, patient came back to emergency room and abdominal imaging studies were conducted which showed that patient had intramural duodenal hematoma associated with gastric outlet obstruction and pancreatitis. Hematoma was the cause of acute pancreatitis as pancreatic enzymes levels were normal at the time of first presentation, but later as the hematoma grew in size, it caused compression of pancreas and subsequent elevation of pancreatic enzymes. We experienced a case of pancreatitis which was caused by intramural duodenal hematoma. This case was missed on initial evaluation. We suggest that physicians should be more vigilant about this condition.